Occurrence of aflatoxin M1 in bovine milk samples consumed in different regions of Brazil - Shundo, Luzia (2016)
Two hundred and fifty-seven samples of milk proceeding from different geographical regions of Brazil were analyzed for determining the presence of aflatoxin M1 (AFM1). The AFM1 extraction was carried out using immunoaffinity column, separated by reversed-phase (C-18) high performance liquid chromatography (HPLC), and quantified by fluorescence detector. The Limits of Quantification (LOQ) were 0.008 μg/kg and 0.080 μg/kg to the fluid and the powder milk, respectively. AFM1 were detected in 209 (81.3 %) samples, being 26 (63.4 %), 105 (84.0 %) and 78 (85.7 %) of pasteurized, UHT (Ultra-high Temperature) and powder milk, respectively. The highest concentration of AFM1 in powder milk was found in one sample from Minas Gerais (1.210 μg/kg). In UHT and pasteurized milk, the highest levels were detected in one sample from Sergipe (0.120 μg/kg) and one sample from Goiás (0.050 μg/kg), respectively. None of the samples analyzed in this study exceeded the Brazilian legal limits for AFM1.